Investigation on electrical properties of BCZT ferroelectric ceramics prepared at various sintering conditions. Issue 187 (12th February 2018) - Buatip, N.; Promsawat, N.; Pisitpipathsin, N.; Namsar, O.; Pawasri, P.; Ounsung, K.; Phabsimma, K.; Rattanachan, S. T.; Janphuang, P.; Projprapai, S.
ABSTRACT: The influence of sintering conditions on phase formation, density, microstructure and electrical properties of BCZT ceramics wer investigated. The BCZT (Ba0.85 Ca0.075 Zr0.1 Ti0.9 O3 ) ceramics were fabricated by a mixed oxide synthetic route of BaCO3, CaCO3, ZrO2 and TiO2 precursors and then sintered at 1250, 1300 and 1350°C for 2 and 4 hrs. Phase formation, densification, microstructure surfaces, dielectric properties, ferroelectric and piezoelectric properties were analyzed by using X-ray diffraction (XRD), Archimedes method, Scanning Electron Microscopy (SEM), LCR Meter, P-E hysteresis and d 33 meter, respectively. In processes of sintering, the results show that BCZT structures are perovskite with pseudo-cubic phase. Sintering condition at 1300°C for 4 hrs exhibits optimum density, grain size and higher electrical properties: density 5.62 g/cm 3 (∼98% of theoretical density), average grain size = 2.19 ± 0.87 µm, dielectric constant (ϵr ) = 2840, dielectric loss (tan δ) = 0.10, remanent polarization ( P r ) = 5.84 µC/cm 2 and d 33 = 167 pC/N.